Surface artery volume pulse wave measurement - verification of a new method - Korpas, David; Halek, Jan; Chlupova, Ludmila (Biomedical papers, 2003)
The aim of this paper is to prove the possible reproducibility of measurement with a new developed device for artery elasticity monitoring and determining the standard of major pulse wave parameters. As a measurement sensor, a conic probe with thin convex membrane was used. This technique allows setting an arbitrary pressure to a measured surface artery. We measured pulse waves on the radial arteries of 108 individuals. We expected similar features in arterial wall elasticity. We concentrated primarily on the amount of subcutaneous fat. For the measured waves we evaluated five following pulse wave parameters: relative crest time, elasticity index, dicrotic wave attenuation, dicrotic wave time and interwave distance. There were no significant differences in measured pulse wave parameters among the tested groups of subjects.
Keywords: Pulse wave / Forearm blood flow / Plethysmography / Arterial elasticity / Blood volume / Measurement techniques